Development of low-cost process for pore generation in cellulose acetate by utilizing calcium salts - Lee, Hwa Jin; Cho, Younghyun; Kang, Sang Wook (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
Pore generation of 1:0.4mol ratio CA/CaCl2 membrane by water-forces into water-channel. [Display omitted] Polymer composite films with straight pores with nano-sized pores were prepared by the water-pressure method. Cellulose acetate was selected as a polymeric support because of accessibility, inexpensive and good thermal stability. For low cost processes, relatively inexpensive metal salt CaCl2 was used as an additive. Added CaCl2 increased the flexibility of the polymer chain. Due to this plasticization, it had been found that when the film was exposed to water pressure, the pore size could be easily adjusted by pressure. In addition, the thermal and mechanical stability of the film was improved by Ca remaining after crosslinking with the polymer chain after water treatment. These pores were confirmed by scanning electron microscopy (SEM) and mercury absorption method. And the interaction between polymer and CaCl2 was confirmed by FT-IR and TGA analysis.